Navigating Copyright for Libraries : Purpose and Scope - Jessica Coates; Victoria Owen; Susan Reilly (De Gruyter Saur, 2022)
Information is a critical resource for personal, economic and social development. Libraries and archives are the primary access point to information for individuals and communities with much of the information protected by copyright or licence terms. In this complex legal environment, librarians and information professionals operate at the fulcrum of copyright's balance, ensuring understanding of and compliance with copyright legislation and enabling access to knowledge in the pursuit of research, education and innovation. This book, produced on behalf of the IFLA Copyright and other Legal Matters (CLM) Advisory Committee, provides basic and advanced information about copyright, outlines limitations and exceptions, discusses communicating with users and highlights emerging copyright issues. The chapters note the significance of the topic; describe salient points of the law and legal concepts; present selected comparisons of approaches around the world; highlight opportunities for reform and advocacy; and help libraries and librarians find their way through the copyright maze.